The effectiveness of blended learning on plant development structure lectures - Eko Retno Mulyaningrum; Rivanna Citraning Rachmawati (JURNAL BIOEDUKATIKA, 2020)
The changes in college curriculum that refers to the Indonesian National Qualifications Framework has consequences on curriculum changes in the Biology Education Study Program of Universitas PGRI Semarang, so that there are adjustments in the course of Plant Anatomy which were initially 2 SKS and Plant Morphology which was initially 2 SKS into one course, Plant Development Structure, with the weight of 3 SKS, so that effective learning is needed by blended learning. Based on this background, the purpose of this study was to determine the effectiveness of blanded learning in Plant Development Structure courses. The learning design uses a combination of face to face methods with offline teaching materials using flipbooks, online discussions with Facebook groups and e-assessment using proprofs software. This research method is pre-experiment with the design of the One Group Pretest Posttest. The results of the pretest obtained an average value of 41.84, while the posttest results obtained an average value of 70.97 and the results of the t-test showed that there were significant differences. In the questionnaire results obtained data as many as 43% of students like blanded learning; 57% of students stated the advantage of using online discussion was to get direct experience as a teacher candidate using social media as a learning medium; 57% of students stated that offline teaching materials can balance the right and left brains; and 60% of students said by e-assessment to get the correct feedback directly. The conclusion is blanded learning that combines face to face, online discussions, offline teaching materials, and e-assessment, and effective blanded learning for Plant Development Structure lectures.